DELAYED-ONSET AMIODARONE-INDUCED THYROTOXICOSIS - Othman, Abdul Rahim Mohd; Nordin, Hidayatil Alimi Keya; Abdullah, Noor Rafhati Adyani (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Amiodarone is a commonly used antiarrhythmic drug for treatment of refractory tachyarrhythmias. However, its use can lead to development of amiodarone-induced thyrotoxicosis (AIT). AIT is classified into type 1, a form of iodine-induced hyperthyroidism, and type 2, which is a drug-induced destructive thyroiditis. AIT can be difficult to treat because of the long half-life of amiodarone. We describe a patient who developed AIT 15 months following cessation of amiodarone. CASE A 58-year-old male presented with sudden onset palpitations and hand tremors. He had history of ventricular tachycardia, for which he had undergone Implantable Cardiac Device (ICD) insertion. He had been on amiodarone for two years, from September 2021 to February 2023, following which the medication was discontinued. At the time of admission, amiodarone had been stopped for 15 months. On examination, he was tachycardic with heart rate of 150/min. The electrocardiogram (ECG) showed sinus tachycardia with spontaneous ICD shock. Thyroid function test indicated TSH <0.08 m IU/L (0.35-4.95), FT3 11.8 pmol/L (2.9-4.9), and FT4 >64 m IU/L (9.01-19.05). T4/T3 ratio was >4. Considering the patient’s history of amiodarone use, a diagnosis of AIT was established. The patient was prescribed carbimazole 30 mg daily and fT4 remained >64 m IU/L after 1 week. Prednisolone 40 mg daily was added to treat mixed AIT 1 and 2. Thyroid ultrasonography revealed heterogeneous echogenicity in both thyroid lobes, with no focal lesion. Doppler study demonstrated a normal pattern of vascularity. The thyroid peroxidase antibody was 185 IU/L (<35) and the patient is currently awaiting thyroid scintigraphy. CONCLUSION The differentiation between type 1 and type 2 AIT can be challenging and indistinct, and some patients exhibit mixed forms of AIT. In such cases, combination therapies are often employed. It is critical to emphasize the importance of maintaining a high index of suspicion for AIT, irrespective of treatment duration or the time elapsed after discontinuation of amiodarone, due to the prolonged half-life of the drug.